Kajian Gender Terhadap Undang-Undang Nomor 1 Tahun 1974 Dan Kompilasi Hukum Islam Menuju Pembaharuan Hukum Perkawinan Islam Di Indonesia - ,, Zeni Lutfiyah (PARENTAL, 2015)
AbstractThis study aims to know what are the forms of gender inequality in the Marriage Law in Indonesia contained in Law No. 1 1974 And Compilation of Islamic Law, to obtain a conceptual and juridical alternative as a solution for the Islamic marriage law reform in Indonesia in line of demandof the dynamics of community.The types this study is a normative juridical studies, that is examines the legal normative clauses of a rule of positive law, using benchmarks doctrine / principle of Islamic law is the main means of basic conceptual formation, determination and assessment of Islamic law. This study uses normative methodological approach. Normative mainly used to analyze the legal formulations and harmony with each other and methodological mainly used to analyze the validity of the conceptual formulation of this law in front of the benchmarks used.The analysis used in the study is a normative legal analysis with engineering validation assessment. This analysis is done by examining normative research topic is then juxtaposed with the arguments and methods of Islamic law determination. It is also possible to do a comparison by examining many aspects, , terms, pillars, and other factors that can determine the legal status of this research topic.Keywords: Gender Studies, Human Right, Marriage, Islamic Law